Humanization in health graduation courses: challenges for implementing national guidelines (Research, Society and Development, 2022)
The National Humanization Policy (PNH) brought up the need to insert humanization in the training of health professionals. Humanization in health seeks to promote the encounter of individuals and their subjectivities, based on caring and providing assistance for others. This study aims to investigate the Political-Pedagogical Projects (PPP) of undergraduate health-related courses and present a survey about the discussion of Humanization in those programs at the Federal University of Paraíba (UFPB). The following documents were consulted through the Integrated System for the Management of Academic Activities: PPP, updated curriculum and syllabus of the Health Sciences Center and the Medical Sciences Center courses. Readings were made in search of the term humanization. In conclusion, there is minimum discussion about humanization in the PPP of healthcare courses at UFPB. Despite being a Unified Health System’s policy that regulates the teaching on humanization for over ten years, UFPB health-related programs have not yet been fully adapted to the purpose of this policy.